2019
DOI: 10.2147/hiv.s200120
|View full text |Cite
|
Sign up to set email alerts
|

<p>Undernutrition and associated factors among HIV-positive adult patients enrolled in antiretroviral therapy (ART) clinics in the Arba Minch area, southern Ethiopia</p>

Abstract: Background: Undernutrition constitutes an important threat to the success of HIV programs in sub-Saharan Africa, and failure to effectively address it may jeopardize the benefits gained so far in the fight against HIV. The aim of the study was to assess undernutrition and associated factors among HIV-positive adult patients enrolled in antiretroviral therapy (ART) clinics in Arba Minch area, south Ethiopia. Methods: A facility-based cross-sectional study was conducted in 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
19
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 30 publications
10
19
2
Order By: Relevance
“…The study was intended to assessing magnitude of under nutrition and associated factors. The study indicated the magnitude of under nutrition was 18.8% (95%, CI (15.1%-23%), it is in line with study conducted in Arba minchi(18.2%) (38), Study conducted in south Africa(18.2%) (38), study conducted in Asella (18.3%) (44) and in Addis Ababa (15.1%) (24). The nding is in line with study conducted in Addis Ababa might be due to similarity in socio-economic level and health service accessibility.…”
Section: Discussionsupporting
confidence: 87%
“…The study was intended to assessing magnitude of under nutrition and associated factors. The study indicated the magnitude of under nutrition was 18.8% (95%, CI (15.1%-23%), it is in line with study conducted in Arba minchi(18.2%) (38), Study conducted in south Africa(18.2%) (38), study conducted in Asella (18.3%) (44) and in Addis Ababa (15.1%) (24). The nding is in line with study conducted in Addis Ababa might be due to similarity in socio-economic level and health service accessibility.…”
Section: Discussionsupporting
confidence: 87%
“…According to this study the prevalence of under-nutrition was close to that of a study conducted in various parts of Ethiopia; 30% in hospitals in the east Harerge zone (12), 25.2% in Butajira hospital (24), and 27% in Nekemte referral hospital (25), However the prevalence of this study was lower than 60.2%, west Gojam zone public hospitals (17), 46.8% in Jimma University specialized hospital (16) 43% in south west Oromia region (14), and higher than study conducted in 12.3% in Dilla university hospital (26) 18.2% in Arba Minch area public health facilities (15).…”
Section: Discussioncontrasting
confidence: 61%
“…Patients who use any substance in the last three months were four times more likely develop under nutrition as compared to those who had not use. Study done in Arbamnch and Canada showed that Current tobacco-smoking adults enrolled in ART programs were at higher risk of being undernourished (15,30). However, study in Nepal showed behavioral factors like alcohol and smoking were found to have no association with under nutrition (31).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations